Влияние летования прудов на инвазию карпа гельминтами - Ивасик, В.М.; Карпенко, И.М.; Кулаковская, О.П. (Вестник зоологии, 1969)
During 1949—1966 the effect of pond being unflooded on the change of carp helmin-thofauna in fishery farms of different climatic zones was studied. It was established that during the first year after the pond was unflooded an amount of helminths species decreases and only after three year exploitation of ponds it increases again. Helminths with a simple development appear the first after the pond was unflooded and the ones with a complex development appear in two-three years. Unflooded position of the ponds favours a three-five fold increase of their fish production during the first years of exploitation.